A avaliação externa simais e a prática pedagógica no ensino de matemática: implicações e proposta didática - Oliveira, José Roberto de (Universidade Federal Rural do Semi-Árido, 2021)
Mathematics has always been part of human life because of its importance in everyday life. Therefore, it is necessary to acquire knowledge that allows each individual the ability to use it in different situations. Thus, the school in these modern times plays an increasingly important role in the lives of students: which is to prepare them for the challenges of a world permeated by technology, new mathematical languages and with that, the need arises for students to know interpret, relate didactic theory to practice, build meanings, solve problems. Which contributes to concerns that are present in our work as a teacher in the discipline of mathematics. Bearing in mind that the lack of interest of many students still lingers, the low rate of performance in the discipline, identified through the evaluation, emerges this research. The objective of this research is, therefore, to contribute, mainly, for the improvement of the performance indexes of the external evaluation SIMAIS of the research field school. The theoretical contribution was based on the theoretical assumptions of Pais (2006), Luckesi (2013), Brasil (2018), France (2010), among others. Through a qualitative, descriptive interpretive and applied research, we seek to intervene in our own pedagogical practice, also configuring itself in an action research. Through this methodological path, we obtain and make considerations about the applied, simulated corpus aimed at students, so that we can make reflections on one of the factors that surround the teaching-learning process, which is the external evaluation - SIMAIS. The participants are 25 students from the 9th grade of elementary school in a public school. And the instrument used was a simulated one endorsed in the SIMAIS test, through an intervention. The intervention process was applied through three pedagogical workshops, delivered remotely through the Google Meet application. The analysis of the intervention process allowed us to conclude that it is important to continuously evaluate, giving real importance to the results of the external evaluation to reflect on the practice itself and rethink new strategies to ensure the students' learning. The intervention carried out showed us clearly that it is necessary to innovate in order to arouse more interest from students, requiring the insertion of technological tools, playful materials and physical spaces that arouse curiosity, mediation of contents and, thus, promote the production of mathematical knowledge. We can say that our work contributed to the students to see mathematics as a subject that is easy to understand, but also the recognition of evaluation as an important tool for self-assessment
Keywords: Matemática; Intervenção Pedagógica; Ensino Remoto Emergencial; SIMAIS; Mathematics; Pedagogical intervention; Emergency remote teaching; SIMAIS; CIENCIAS EXATAS E DA TERRA::MATEMATICA